Pivotal Thinking and its Correlation to Linguistic-Verbal Intelligence of First-Stage student of Intermediate school in the (Journal of the College of Basic Education, 2025)
The purpose of the study is to determine the pivotal thinking skills and how they are related to verbal linguistic intelligence in First-Stage of Intermediate school math students. 400 students from various schools that are affiliates of the General Directorate of Education of Baghdad/Alrusafa II made up the research sample. The researcher used the Aladhami (2018) pivotal thinking test and drew on prior research and literature to prepare the verbal linguistic intelligence scale's paragraphs. The data were compared using Pearson's correlation coefficient and Test (1). The findings revealed that :1.There is a statistically significant difference at a significance level of (1000) between the hypothetical mean and the arithmetic mean of the scores of First-Stage student of Intermediate school in the pivotal thinking test and the verbal linguistic intelligence scale and the valid arithmetic meanThere is a statistically significant positive correlation between the scores of First-Stage student of Intermediate school in choosing pivotal thinking and their scores in the verbal linguistic intelligence scale.Based on the finding of the research, the researcher concluded that the level of First-Stage student of Intermediate school is good in choosing pivotal thinking and the verbal linguistic intelligence scale and a positive correlation between pivotal thinking and verbal linguistic intelligence ,and recommended a number of recommendations and suggestions